French constitutional law : cases and materials - Rogoff, Martin A. (Durham, North Carolina : Carolina Academic Press, 2014)
"French Constitutional Law: cases and materials includes extracts from decisions of the Constitutional Council and Council of State, significant laws, important reports, and a variety off french legal writings". -- BACKCOVER.
The Fifth Republic : political institutions and separation of powers -- The constitutional Council -- Republican principles -- International and European law.
Includes bibliographical references (pages 517-528) and index.
Keywords: France; Constitutional law -- France; Casebooks (Law)